Legal protection of indigenous communities from natural resource exploitation: a comparative study of Indonesia and the Philippines - Hairunnisa Rahmi Fadiyah; Fadhel Ally Muhammad (Journal of Law, Politic and Humanities, 2026)
The large-scale exploitation of natural resources in Southeast Asia has generated a wide range of legal, social, and ecological challenges, particularly for indigenous communities living in resource-rich areas. This article seeks to analyze and compare the forms of legal recognition and protection afforded to indigenous peoples in Indonesia and the Philippines, with a focus on their sovereignty over customary lands and their participation in decision-making processes related to natural resource governance. Employing a normative and comparative legal approach, the study examines statutory frameworks, judicial decisions, and selected case studies involving the Moi people in Papua (Indonesia) and the Lumad communities in Mindanao (Philippines). The findings indicate that, although both countries formally recognize the existence and rights of indigenous peoples, the extent of legal protection and its implementation differs significantly. The Philippines adopts a more explicit and progressive legal framework through the Indigenous Peoples’ Rights Act (IPRA), which recognizes collective land ownership and upholds the principle of Free, Prior, and Informed Consent (FPIC). In contrast, Indonesia relies largely on administrative recognition and lacks a legally binding FPIC mechanism within its national legislation. Despite these differences, indigenous peoples in both countries continue to face substantial challenges, including criminalization, militarization, and marginalization from development processes. This article therefore recommends strengthening national legal frameworks particularly through the enactment of a comprehensive Indigenous Peoples Law in Indonesia, institutional reforms of oversight bodies in the Philippines, and the promotion of ecological and participatory justice in natural resource governance.